2003
DOI: 10.1029/2002je001985
|View full text |Cite
|
Sign up to set email alerts
|

Ages and stratigraphy of mare basalts in Oceanus Procellarum, Mare Nubium, Mare Cognitum, and Mare Insularum

Abstract: [1] Accurate estimates of mare basalt ages are necessary to place constraints on the duration and the flux of lunar volcanism as well as on the petrogenesis of lunar mare basalts and their relationship to the thermal evolution of the Moon. We performed new crater size-frequency distribution measurements in order to investigate the stratigraphy of mare basalts in Oceanus Procellarum and related regions such as Mare Nubium, Mare Cognitum, and Mare Insularum. We used high-resolution Clementine color data to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
486
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(505 citation statements)
references
References 44 publications
16
486
3
Order By: Relevance
“…Spectrally, large parts of Mare Insularum are influenced by basalt lavas of low to moderate TiO 2 content on which ejecta of the craters Copernicus, Kepler, and Eratosthenes are superimposed (Hiesinger et al, 2003). The geologic map by Wilhelms and McCauley (1971) shows that most basalts of this region are Imbrian mare materials with some units showing characteristics of Eratosthenian mare (Em) material.…”
Section: [Figure 1]mentioning
confidence: 99%
“…Spectrally, large parts of Mare Insularum are influenced by basalt lavas of low to moderate TiO 2 content on which ejecta of the craters Copernicus, Kepler, and Eratosthenes are superimposed (Hiesinger et al, 2003). The geologic map by Wilhelms and McCauley (1971) shows that most basalts of this region are Imbrian mare materials with some units showing characteristics of Eratosthenian mare (Em) material.…”
Section: [Figure 1]mentioning
confidence: 99%
“…On the Moon, impact melt deposits line the floor and interior of fresh basins (such as Orientale) that have not been subsequently filled extensively with lava (e.g., Head, 1974b;Howard et al, 1974;Spudis, 1993). The majority of lunar basins, however, have been subsequently filled with mare basalts (e.g., Hiesinger et al, 2000Hiesinger et al, , 2003, and one might infer that if the basin appears filled, and the original basin rings buried and obscured, the original deposit of impact melt has been covered by subsequent lava flooding. Calculations strongly suggest, however, that impact melt is proportionally more important in larger basins (Cintala and Grieve, 1998) and at higher impact velocity (Cintala, 1992), specifically that the volume of impact melt formed relative to that of the crater will grow, and proportionally more will be retained inside the basin rim (Cintala and Grieve, 1998;Pierazzo et al, 2007).…”
Section: Evidence For Volcanic Filling Of the Caloris Basin Interiormentioning
confidence: 99%
“…7). MESSENGER data from the first Mercury flyby were of insufficient resolution and illumination geometry to document the morphologic features that might reveal sequential emplacement of plains units over time, and the prominent color contrasts between volcanic units within Imbrium (see Hiesinger et al, 2000Hiesinger et al, , 2003 are not observed in Caloris Robinson et al, 2008). Thus, a major goal for MESSENGER orbital operations will be the acquisition of imaging and spectral data to characterize and date the range of volcanic units in the interior.…”
Section: Evidence For Volcanic Filling Of the Caloris Basin Interiormentioning
confidence: 99%
“…In lunar maria, wrinkle ridges occur predominantly in the basin interior, and graben are found near the margins or outside of mascon mare basins (McGill, 1971;Strom, 1972;Maxwell et al, 1975;Golombek, 1979;Solomon and Head, 1980;Watters and Johnson, in press). Moreover, superposition relationships of lunar graben suggest that they are restricted to the older mare basalt units, whereas wrinkle ridges deform both older and younger mare basalt units (Boyce, 1976;Lucchitta and Watkins, 1978;Hiesinger et al, 2003;Watters and Johnson, in press). Crosscutting relationships between wrinkle ridges and graben in Caloris indicate that extension postdates contraction of the floor, in contrast to the sequence of stresses implied for lunar basins.…”
Section: Tectonicsmentioning
confidence: 99%